Taking on technocracy : nuclear power in Germany, 1945 to the present - Augustine, Dolores L. (Protest, culture and society, 2018)
Introduction -- Nuclear dreams and radioactive nightmares: popular culture and the quest for nuclear consensus in East and West Germany, 1945-1970 -- On the brink of disaster?: safety regimes and nuclear accidents in the two Germanys -- Dissenting voices: the emergence of counter-experts in West Germany -- From local roots to national prominence: the struggle over Wyhl -- Environmentalism as civil war: Brokdorf-and the consequences -- The shock of Chernobyl and the environmentalist breakthrough in West Germany -- Not immune to error: Chernobyl's impact in the GDR -- Abandoning nuclear power-or not? -- Conclusion